2018
DOI: 10.1021/acs.jced.8b00323
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Thermodynamic Models for Ternary Liquid–Liquid Equilibrium Systems {Water + Polyoxymethylene Dimethyl Ethers +4-Methyl-2-pentanol} at Different Temperatures

Abstract: Polyoxymethylene dimethyl ethers (DMM n ) have attracted particular attention in industry as excellent oxygenated fuel additives. This study aims to reveal the liquid−liquid equilibrium (LLE) values regarding ternary mixtures {water + methylal (DMM 1 ) + 4-methyl-2-pentanol (MIBC)}, {water + DMM 2 + MIBC}, {water + DMM 3 + MIBC}, and {water + DMM 4 + MIBC} at 298.2 and 308.2 K under 101.3 kPa. Distribution factor and selectivity were utilized to assess the extracting capabilities of the selected extractant. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…As shown in Table , the distribution coefficients and separation factor values for the studied systems are all greater than 1, which indicates the extraction capability of toluene to extract PODE n from aqueous phase and toluene as an ideal solvent. As shown in Figure , the distribution coefficient for the ternary LLE equilibrium systems are not constant, which is consistent with the reported research. ,, The distribution coefficient at 303.15 K is higher than at 293.15 K, indicating that the extraction capacity of the extractant increases with increasing temperature. ,, As can be seen in Figure , the separation factors decreased with the increase of the mass fraction of PODE n in aqueous phase and hence as a result of the mass fraction of water in organic phase was also increased . Meanwhile, the separation factor of four studied systems decreased with the increasing temperature and the influence of temperature on the separation factor was slight. , As the ratio of feed (water + PODE n ) to toluene increases, the separation capacity of the solvent decreases.…”
Section: Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Table , the distribution coefficients and separation factor values for the studied systems are all greater than 1, which indicates the extraction capability of toluene to extract PODE n from aqueous phase and toluene as an ideal solvent. As shown in Figure , the distribution coefficient for the ternary LLE equilibrium systems are not constant, which is consistent with the reported research. ,, The distribution coefficient at 303.15 K is higher than at 293.15 K, indicating that the extraction capacity of the extractant increases with increasing temperature. ,, As can be seen in Figure , the separation factors decreased with the increase of the mass fraction of PODE n in aqueous phase and hence as a result of the mass fraction of water in organic phase was also increased . Meanwhile, the separation factor of four studied systems decreased with the increasing temperature and the influence of temperature on the separation factor was slight. , As the ratio of feed (water + PODE n ) to toluene increases, the separation capacity of the solvent decreases.…”
Section: Results and Discussionsupporting
confidence: 86%
“…21−25 Due to low vapor pressure, density, viscosity, and capability to form two phases, 26,27 toluene can be used as an appropriate solvent for extracting the PODE n from aqueous solution. Shi et al 28 20 studied the LLE in binary and ternary mixtures containing water, formaldehyde, methanol, and PODE n in the temperature range of 280−240 K. Wang et al 29 investigated the LLE for ternary systems of water + PODE n + 4-methyl-2-pentanol at 298.2 and 308.2 K. By comparing their experimental data of distribution coefficient (D) and separation factor (S), it can be found that the extraction ability of aromatic extractants (pxylene and toluene, etc.) is better than 4-methyl-2-pentanol (MIBC), since the excellent hydrophobicity of aromatic hydrocarbons is better than MIBC.…”
Section: Introductionmentioning
confidence: 99%
“…The partition coefficient, D , and the separation factor, S , are used to assess the separation efficiency about furfural and DMF, and the formula for calculating D and S : where w 1 II and w 1 I are the concentrations of n -hexane in the solvent phase and n -hexane phase, respectively. w 2 II and w 2 I indicate the mass fractions of 1-hexene in the two phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The operations were done in a specific laboratory setup, and the details are dispensed below. , First, the mixture of a certain concentration is added to a 50 mL impenetrable glass equilibrium cell. After the stationary phase, equilibrated kettle and circulating water were vigorously stirred for 4 h, and the composite system was maintained for at least 6 h to achieve system stability.…”
Section: Methodsmentioning
confidence: 99%